De um corpo para outro: o arquivo cine-performativo de Naomi Kawase - Oliveira, Eduardo dos Santos (2018)
Based on a conceptual reflection that aims to put in dialogue theories from the field of cinema and performance studies, this dissertation intends to visit the self-referential cinema of the japanese diretor Naomi Kawase, more specifically the film Embracing (Ni Tsutsumarete, 1992), in attempt to investigate the performative practices that the film-maker undertakes in (and with) the image and how she inscribes her own body in the materiality of the film, thereby presenting what in this work we call a “cine-performative archive” . In order to elaborate this concept, the present text is mainly based on readings of the authors Elena Del Rio (2012), to consider the performance in the cinema from the affective power that emerges from the encounter between filmic body and spectator’s body, and Diana Taylor (2013) , regarding the archive as the performative’s material dimension. Each gesture shot by Kawase germinates new situations, forges new events, (re)creates realities, keeps alive and activates her family’s memories by moving it in time. At the end of the process, another archive, of cinematographic and performative qualities, is then produced: the film itself, which, in turn, reconfigures the repertoire of those who stand before it and offers them it’s desire in exchange for living the desire from the other.